Modelisation du comportement mecanique de cables metalliques - Durville, Damien (European Journal of Computational Mechanics, 1998)
The mechanical behaviour of a wire rope depends highly on the interactions between its elementary wires. We suggest to model this behaviour by the mean of the finite element method, considering the wire rope as an assembly of rods undergoing large deformations and submitted to contact-friction interactions. An enriched kinematical beam model is used to take into account the eff ects of transverse strains in the wires. A special emphasis is put on the modeling of contact, based on an a priori discretization of the contact proble . independently of the finite element discretization of the structure. Numerical results are given to prove the efficiency of the approach.